2014
DOI: 10.1002/chem.201304500
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Electrogenerated Chemiluminescence Efficiency in Blue‐Shifted Iridium(III)‐Complexes: An Experimental and Theoretical Study

Abstract: Compared to tris(2-phenylpyridine)iridium(III) ([Ir(ppy)3 ]), iridium(III) complexes containing difluorophenylpyridine (df-ppy) and/or an ancillary triazolylpyridine ligand [3-phenyl-1,2,4-triazol-5-ylpyridinato (ptp) or 1-benzyl-1,2,3-triazol-4-ylpyridine (ptb)] exhibit considerable hypsochromic shifts (ca. 25-60 nm), due to the significant stabilising effect of these ligands on the HOMO energy, whilst having relatively little effect on the LUMO. Despite their lower photoluminescence quantum yields compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 79 publications
5
71
0
Order By: Relevance
“…However, a stronger donor ligand in the iridium(III) complex rather increased the ECL response in the present work. It is reported that the lower the energy level of the LUMO (lowest unoccupied molecular orbital) of the iridium complex, the more efficient ECL process, and thus higher ECL response [28]. In this work, the energy level of the LUMO obtained from electrochemical studies are not well correlated with the observed ECL intensity.…”
Section: Ir Dfppymentioning
confidence: 75%
See 2 more Smart Citations
“…However, a stronger donor ligand in the iridium(III) complex rather increased the ECL response in the present work. It is reported that the lower the energy level of the LUMO (lowest unoccupied molecular orbital) of the iridium complex, the more efficient ECL process, and thus higher ECL response [28]. In this work, the energy level of the LUMO obtained from electrochemical studies are not well correlated with the observed ECL intensity.…”
Section: Ir Dfppymentioning
confidence: 75%
“…Lee and coworkers reported the synthesis and characterization of new iridium complexes of (pq) 2 Ir(acac) and (pq) 2 Ir(tmd) (pq = 2-phenylquinoline anion, acac = acetylacetonate anion, and tmd = 2,2′,6,6′-tetramethylhepta-3,5-dione anion) with much higher ECL efficiencies at 589 and 593 nm compared to that of Ru(bpy) 3 2+ [16]. Subsequently, a large number of novel iridium(III) complexes with various ligands have been prepared for ECL studies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In particular, heteroleptic iridium(III) complexes such as Ir(dfppy) 2 (bpy) [27] and Ir(dfppy) 2 (PyBiz) [32] (dfppy = 2-(2,4-difluorophenyl) pyridine, PyBiz = 2-(2-pyridyl)benzimidazolato-N,N′) as the primary cyclometalating ligand have shown the highly enhanced ECL response compared to that of Ru(bpy) 3 2+ .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…15,43,[52][53][54] Therefore, from the distinct emission properties, it is more appropriate to assume a mixed MLCT-LC character (Fppy-based) for the T 1 state of FIrMepic, harvested by singlet and triplet relaxations, similarly to FIrpic ( Figure S8 in supporting information). 29 . Data obtained using the three standards are in excellent agreement among them and also to the absolute value, measured using an integrating sphere.…”
Section: Absorptionmentioning
confidence: 95%
“…In comparison with the classical Ru(bpy) 3 2? , cyclometalated iridium(III) complexes generally possess much higher photoluminescence (PL) efficiency and easy tunability of the emission color. By modulating the ligand and changing the coordination mode, a series of cyclometalated iridium(III) complexes have been designed, synthesized, and thoroughly investigated through photophysics, electrochemistry, and ECL [23][24][25][26][27]. The development of new ECL emitters with different emission colors makes it possible to simultaneously determine multiplex analytes in clinical diagnostics.…”
Section: Introductionmentioning
confidence: 99%